2011
DOI: 10.1096/fj.11-186460
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric C‐reactive protein modulates classic complement activation on necrotic cells

Abstract: The acute-phase protein C-reactive protein (CRP) recruits C1q to the surface of damaged cells and thereby initiates complement activation. However, CRP also recruits complement inhibitors, such as C4b-binding protein (C4bp) and factor H, which both block complement progression at the level of C3 and inhibits inflammation. To define how CRP modulates the classic complement pathway, we studied the interaction of CRP with the classic pathway inhibitor C4bp. Monomeric CRP (mCRP), but not pentameric CRP (pCRP), bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 54 publications
3
90
0
Order By: Relevance
“…However, tissue-bound mCRP may also modulate classical complement activation by recruiting C4-binding protein [35]. Taken …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tissue-bound mCRP may also modulate classical complement activation by recruiting C4-binding protein [35]. Taken …”
Section: Discussionmentioning
confidence: 99%
“…Such mCRP has been detected in vessels, skeletal muscle, liver and in tissue of chronic renal disease, possibly with extrahepatically produced CRP [29][30][31][32]. The well-known fact that pentameric CRP activates the classical complement pathway, has also been reported to account for mCRP [33][34][35]. Two studies have indeed identified CRP deposited in renal specimens from LN patients by means of conventional immunofluorescence microscopy [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The proposal of disturbed membranes being the major sites for mCRP generation has been further corroborated by elegant studies that demonstrate the binding and dissociation of CRP on the surface of necrotic cells [65,66] and activated platelets [76,79] in a lysoPC-dependent manner [76]. Moreover, Dr. Peter and colleagues [80] recently identified novel pathways for mCRP generation upon binding of CRP to amyloid aggregates, the typical pathological feature found in brains of persons with Alzheimer's disease, and lysoPC-enriched microparticles released by activated cells or isolated from blood of patients with myocardial infarction [81].…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiesmentioning
confidence: 91%
“…Since mCRP (but not CRP) also binds to Factor H, the activation of CCP by mCRP is largely restricted to the opsonic C3 level without proceeding to the more inflammatory C5 stage [60]. Subsequent studies confirmed the enhanced interactions of mCRP with modified lipoproteins [61] and complement [62][63][64][65][66][67] and further revealed the important contributions of mCRP in promoting non-inflammatory clearance of apoptotic or necrotic cells by controlling complement activation on the cell surface through balanced recruitment of C1q, Factor H and C4bp [64][65][66]. Because inappropriate handling of CRP, including lyophilization [68], storage in the absence of calcium [69] and immobilization onto microtiter wells [60,70], leads to the disruption of the pentameric structure, the reported properties of CRP suffering these technical pitfalls should be re-evaluated with Factor H interaction as a prominent example [60,64,71].…”
Section: The Bioactivities Of Crp Are Dependent On Conformational Statesmentioning
confidence: 99%
See 1 more Smart Citation